Structural engineering formulas - Mikhelson, Ilya.; Hicks, Tyler Gregory, 1921- (New York : McGraw-Hill Education, 2013)
Thoroughly revised with more than 300 new formulas, this compact yet comprehensive compilation puts essential data related to the design and analysis of engineering structures at your fingertips. Structural Engineering Formulas, Second Edition covers a wide range of topics, including statics, soils, foundations, retaining structures, pipes, and tunnels, and explains the use and application of each ready-to-use formula. This time-saving reference for civil engineers is also invaluable to students and those studying for licensing exams.
Part I. Basis of Structural Analysis -- Stress and Strain : Methods of Analysis -- Properties of Geometric Sections -- Part II. Statics -- Beams : Diagrams and Formulas for Various Loading Conditions -- Frames : Diagrams and Formulas for Various Static Loading Conditions -- Arches : Diagrams and Formulas for Various Loading Conditions -- Trusses : Method of Joints and Method of Section Analysis -- Plates : Bending Moments for Various Support and Loading Conditions -- Part III. Soils and Foundations -- Soils -- Foundations -- Part IV. Retaining Structures, Pipes, and Tunnels -- Retaining Structures -- Pipes and Tunnels : Bending Moments for Various Static Loading Conditions -- A. Quick-Use Conversion Tables -- B. Mathematical Formulas: Algebra -- C. Mathematical Formulas: Geometry, Solid Bodies -- D. Mathematical Formulas: Trigonometry -- E. Symbols.
Includes index.
Keywords: Structural engineering -- Mathematics; Mathematics -- Formulae